2022
DOI: 10.26740/bisma.v15n1.p96-118
|View full text |Cite
|
Sign up to set email alerts
|

The effect of entrepreneurship orientation and flexibility toward adaptive innovation and improved firm performance

Abstract: This study analysed the effect of entrepreneurial orientation and flexibility on adaptive innovation and firm performance. The sample of this study consisted of 114 orchid business actors. The data analysis technique used in this study uses quantitative methods with the SEM analysis method (WarpPLS) as an analytical tool to process data. Data was collected by direct interview and through a Google Form. This study proves that entrepreneurial orientation directly and positively affects firm performance and adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Conversely, the lower the level of entrepreneurial orientation implemented in SMEs in Padang City, the lower the level of performance of SMEs. The finding of this study is in line with several previous studies which found that entrepreneurial orientation had a positive and significant effect on the performance of SMEs (Alvarez-Torres et al, 2019;Cuevas-Vargas et al, 2019;Rofiaty et al, 2022;Sakib et al, 2022;Sefnedi et al, 2022).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Conversely, the lower the level of entrepreneurial orientation implemented in SMEs in Padang City, the lower the level of performance of SMEs. The finding of this study is in line with several previous studies which found that entrepreneurial orientation had a positive and significant effect on the performance of SMEs (Alvarez-Torres et al, 2019;Cuevas-Vargas et al, 2019;Rofiaty et al, 2022;Sakib et al, 2022;Sefnedi et al, 2022).…”
Section: Resultssupporting
confidence: 92%
“…In this study, the entrepreneurial orientation variable was measured by using 5 indicators (Alvarez-Torres et al, 2019) namely innovation, risk-taking, proactiveness, autonomy, and competitive aggressiveness. The results of previous studies explain that the stronger the entrepreneurial orientation, the higher the company's performance (Alvarez-Torres et al, 2019;Cuevas-Vargas et al, 2019;Rofiaty et al, 2022;Sakib et al, 2022;Sefnedi et al, 2022). Based on the results of these previous studies, the study proposed the following hypothesis: H 1 : Entrepreneurial orientation positively affects SMEs' performance…”
Section: Entrepreneurial Orientationmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies have shown that innovation is a key driver of business success. Companies that combine the capacity to innovate with resources are more successful in developing new capabilities and achieving competitive advantage (Rofiaty et al, 2022;Skordoulis et al, 2020).…”
Section: Competitive Advantage and Its Dimensionmentioning
confidence: 99%